2000
DOI: 10.1152/jappl.2000.88.4.1446
|View full text |Cite
|
Sign up to set email alerts
|

Developmental myosin heavy chains in the adult human diaphragm: coexpression patterns and effect of COPD

Abstract: In preliminary experiments we noted developmental (i.e., embryonic and neonatal) myosin heavy chains (MHCs) in the diaphragms of patients with severe chronic obstructive pulmonary disease (COPD). We hypothesized that this finding represented new fiber formation secondary to injury associated with the mechanical stress of COPD or previously undescribed MHCs in the human diaphragm. To distinguish between these possibilities, we analyzed diaphragmatic biopsies obtained from 9 patients with severe COPD (forced exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 46 publications
(48 reference statements)
3
32
2
Order By: Relevance
“…The proportion of MyHC-I fibres in the non-COPD group Glu mmol·kg WW -1 lis somewhat higher than those previously reported by NGUYEN et al [34] and LEVINE and coworkers [6,35] (45 and 41%). This may be related to differences in the criteria used for selection of a control group.…”
Section: Glutathione Concentration In Relation To Fibre Typecontrasting
confidence: 56%
See 1 more Smart Citation
“…The proportion of MyHC-I fibres in the non-COPD group Glu mmol·kg WW -1 lis somewhat higher than those previously reported by NGUYEN et al [34] and LEVINE and coworkers [6,35] (45 and 41%). This may be related to differences in the criteria used for selection of a control group.…”
Section: Glutathione Concentration In Relation To Fibre Typecontrasting
confidence: 56%
“…The possibility that the presence of lung cancer contributes to the slightly higher level of MyHC-I fibres in the diaphragm cannot be totally excluded, although the exact underlying mechanism is difficult to elucidate. NGUYEN et al [34] and LEVINE and coworkers [6,35] included subjects with mild pulmonary impairment undergoing resection of solitary pulmonary nodules and brain-dead organ donors. It is possible that both the underlying lung diseases in the first group and the amount of time in receipt of ventilatory support and the decreased central ventilatory drive due to brain death in the second group may be an important bias.…”
Section: Glutathione Concentration In Relation To Fibre Typementioning
confidence: 99%
“…No fall in Pdi,tw was observed in either study, suggesting that the diaphragm is relatively fatigue resistant in COPD. This is supported by the observation that COPD patients appear to be better at sustaining maximum voluntary ventilation than normal subjects [111] and, indeed, histologically, the cellular adaptations of the diaphragm in COPD show an increased proportion of type I slow muscle fibres or slow myosin heavy-chain isoforms [112]. With this in mind, it is unsurprising that the effects of inspiratory muscle training in COPD remain controversial.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 91%
“…Numerous animal studies using a variety of species (mice, rats, rabbits, and pigs) have reported that prolonged MV results in significant atrophy of diaphragm muscle fibers (16,49,73,78,100,107). However, because the rat and human diaphragm are anatomically alike and contain a similar fiber type composition (76,81), the rat has become the most commonly used animal model to study MV-induced changes in diaphragm fiber size and function. Several studies reveal that as few as 12 h of controlled MV results in a 10 -15% reduction in the cross-sectional area of all rat diaphragm fiber types (i.e., type I, type IIa, and type IIx/b) (67,69,82,103).…”
Section: Mv-induced Diaphragm Atrophymentioning
confidence: 99%